Development of a low-melting-point eutectic salt and evaluation of its discharge performance for light weight thermal batteries. Issue 34 (9th August 2022) - Ahn, Tae-Young; Cheong, Hae-Won; Kang, Seung-Ho; Lee, Jae-In; Kim, Minu; Choi, Yusong
Abstract : This study proposes eutectic salts, containing rubidium chloride, with low melting points to be applied in light weight thermal batteries and also evaluates their performance. Abstract : This paper proposes low-melting-point eutectic salts containing RbCl as electrolytes for light weight thermal batteries. The handleability of the eutectic salts was remarkably improved for commercialisation. Their performance as thermal battery molten-salt electrolytes was verified using tests on a single cell and a 12-cell stacked battery.